105k views
5 votes
Simplify y to the 1/3 ÷ y to the -3/2 y to the 1/2

1 Answer

2 votes


(y^(1)/(3))/(y^(-3)/(2)y^(1)/(2))

The rule of exponent says , when two terms with same base are in multiplication , the exponents gets added.

for example

a^m * a^ n = a^(m+n)

and when two terms are in division with same base , the exponents are subtracted

for example

a^m /a^n = a^(m-n)

So applying these rules

we get


\frac{y^(1)/(3)}{y^{(-3)/(2)+(1)/(2)} }

=
\frac{y^(1)/(3)}{y^{(-2)/(2)}}

=
(y^(1)/(3))/(y^(-1))

=
y^{(1)/(3)-1}

=
y^(-2)/(3)

=
\frac{1}{y^{(2)/(3)}}

User Adam Berman
by
5.3k points